The Relationship between The Big Five Personality and Student’s Time Management - Susanti, Ruth Natalia; Muzakki, Saiful Ni’am; Faqihuddin, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to determine whether there is the relationship between The Big Five Personality on students’ time management. This study also explores The Big Five Personality each traits, which consists of neuroticism, extraversion, openness to experience, agreeableness and conscientiousness on student’s time management. The approach used is quantitative method. The data collection tool uses The Time Management Scale and The Big Five Factor Inventory. The population in this study were college students of Universitas Muria Kudus. The number of samples collected was 59 college students in their sixth semester. The data analysis method consisted of normality test, homogeneity test, and hypothesis testing with Pearson Corellation. The results of the analysis revealed a significant and positive relationships between The Big Five Personality on students’ time management. However, further correlation and regression analysis revealed neuroticism as the most predictive student’s time management but revealed a non-significant relationship. Additionally, only conscientiousness trait showed a significant relationship with student’s time management.